Investigation by top‐down high‐performance liquid chromatography–mass spectrometry of glutathionylation and cysteinylation of salivary S100A9 and cystatin B in preterm newborns. Issue 1 (13th December 2021) - Boroumand, Mozghan; Manconi, Barbara; Serrao, Simone; Iavarone, Federica; Olianas, Alessandra; Cabras, Tiziana; Contini, Cristina; Pieroni, Luisa; Sanna, Maria Teresa; Vento, Giovanni; Tirone, Chiara; Desiderio, Claudia; et al.
Abstract: Glutathionylation and cysteinylation can be involved in the protection of critical cysteines from irreversible oxidative damages. S100A9 long and cystatin B, proteins highly represented in the saliva of preterm and at‐term newborns, can undergo these modifications. Levels of S100A9 long and cystatin B and their glutathionylated and cysteinylated derivatives have been determined by a top‐down platform based on high‐performance liquid chromatography–electrospray ionization–mass spectrometry in 100 salivary samples serially collected from 17 preterm newborns with different postconceptional age at birth (178‐226 days) and in 90 salivary samples collected from at‐term newborns and babies. Results showed that: (1) S100A9 long and cystatin B were mainly present as unmodified forms in extremely preterm newborn; (2) the percentage of the S‐thiolated derivatives of both proteins increased with increasing the postconceptional age; (3) the greatest variation occurred up to about 280 days of postconceptional age. Interestingly, differences in the levels of the S‐thiolated derivatives only depended on the postconceptional age and not on whether the infant was born preterm or at‐term. Inadequate levels of cysteine and glutathione might be responsible for the low level of S‐thiolated derivatives measured in preterm newborns. Data are available via ProteomeXchange with identifier PXD025517.